Integration of Islamic-Based Strategic Management Accounting in Tafsir Ath-Thabari - Ismaulina Chairawan; Dahliana Dahliana; Muhammad Syahrial Razali Ibrahim (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study aims to integrate the principles of shariah in Tafsir Ath-Thabari, such as justice, honesty, trustworthiness, and transparency, into the Islamic-based Strategic Management Accounting (SMA) system. Shariah-based SMA offers a holistic approach to business decision-making, balancing profitability, social responsibility, and environmental sustainability. Utilizing hermeneutic tafsir methods and thematic analysis, this research identifies the relevance of shariah values contained in Surah Al-Baqarah verses 282 and 283. The findings reveal that the principles of justice, honesty, trustworthiness, and transparency in Tafsir Ath-Thabari provide an ethical foundation for SMA, creating a system oriented toward sustainability and ethics. This study develops a shariah-based SMA model encompassing four stages: identification, strategy formulation, implementation, and continuous evaluation. The integration of these shariah values establishes business practices that not only support profitability but also maintain trust, accountability, and positive social impact. Islamic-based SMA is relevant as a solution to modern business challenges, offering a high-integrity framework aligned with shariah principles.